An Extreme Case of Retinal Ischemia - Moleiro, Ana Filipa (2023)
A 30-year-old type-1-diabetic male was referred to our institution for ophthalmic medical care. The patient’s ocular history included bilateral proliferative diabetic re- tinopathy previously treated with peripheral panretinal panphotocoagulation (PRP) and anti-vascular endothelial growth factor (VEGF) intravitreal treatments bilaterally and vitrectomy with silicone oil tamponade on the right eye (OD). At our institution, OD best corrected visual acuity (BCVA) was 20/32 and left eye (OS) BCVA was 20/50. Biomicroscopy was normal bilaterally. OD fundoscopy revea- led intra-ocular silicone oil, fibrotic tissue around vascular arcades, and PRP burns. OS fundoscopy revealed peripa- pillary neovascularization, macular fibrotic proliferation associated to neovascular foci, and incomplete PRP burns. Fluoresceine angiography was performed. A late phase of the OS fluoresceine angiogram is shown, where dye leakage is evident at the optic disc and vascular arcades corresponding to neovascularization, with scatter PRP burns. Peripheral retinal ischemia is extremely severe. Capillary perfusion is observed only at the macular area and extending two disk diameters nasally of the optic disk. No capillary perfusion is observed in the remaining retina. Additional PRP sessions and anti-VEGF treatment were scheduled, besides proper endocrinologic follow-up. This is an impressive case due to the huge area of retinal ischemia, sparing only the central macular and peripapilla- ry areas.